Assessment of patient satisfaction in obstetric care under the LaQshya program - Singh, Archana; Suganya, K.; Mounika, P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Patient satisfaction is a key indicator of healthcare quality, especially in maternity services. The LaQshya program, launched by the Government of India, aims to improve labour room and maternity OT services and ensure respectful maternity care. To assess the effectiveness of the program, study was done to know patient satisfaction with obstetric care among post-delivery women at Government General Hospital, Siddipet. Methods: A prospective cross-sectional study was conducted over 3 months among 1000 postpartum women who stayed for at least 2 days after delivery. A structured questionnaire assessed socio-demographic profile, communication, birthing satisfaction, staff behaviour, hospital facilities, and overall satisfaction. Results: Most patients reported satisfaction with communication (90%), intrapartum care (94%), and staff professionalism (94%). Birthing satisfaction was high, with 100% reporting privacy and permission for a birth companion. Hospital infrastructure satisfaction was 81%, cleanliness 85%, and bed availability 93%. Overall, 83% rated services as “good” and 17% as “excellent.” The mean satisfaction score was 92.5%. Conclusions: Overall patient satisfaction with obstetric services was high, indicating effective implementation of the LaQshya program. Continuous monitoring and targeted interventions can further enhance quality of maternal care.